2006
DOI: 10.1111/j.1365-2265.2006.02652.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyroxine replacement on serum IGF‐I, IGFBP‐3 and the acid‐labile subunit in patients with hypothyroidism and hypopituitarism

Abstract: T4 replacement increases the serum levels of IGF-I and ALS in patients with primary as well as central hypothyroidism. IGFBP-3 levels increase in response to T4 replacement in patients with primary hypothyroidism but not in those with central hypothyroidism, suggesting that thyroid hormones increase IGF-I and ALS but not IGFBP-3 in patients with GH deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
4
20
1
1
Order By: Relevance
“…Hypothyroid humans also have consistently been shown to have a decrease in serum IGF-1 concentration. [67][68][69] Similar decreases in GH and IGF-1 concentration have been reported for hypothyroid rodents as well. 70,71 Dogs appear to be unique in having an increase in circulating GH and IGF-1, compared with other species that have a decrease or no change in these hormones with hypothyroidism.…”
Section: Discussionsupporting
confidence: 67%
“…Hypothyroid humans also have consistently been shown to have a decrease in serum IGF-1 concentration. [67][68][69] Similar decreases in GH and IGF-1 concentration have been reported for hypothyroid rodents as well. 70,71 Dogs appear to be unique in having an increase in circulating GH and IGF-1, compared with other species that have a decrease or no change in these hormones with hypothyroidism.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast to the study performed by Willemsen et al [19], they reported that IGF-1 and resistin levels increased significantly after treatment with GH [20]. Schmid et al detected that T4 replacement increased IGF-1 level in primary and central hypothyroid patients [21]. They reported that administration of thyroid hormone to the patients with GH deficiency increased IGF-1 level [21].…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Bona et al [28] documented that in the patients with hypothyroidism - both congenital and caused by thyroiditis - L-T 4 replacement led to physiological increase of IGF-I and IGFBP-3 secretion. Moreover, Schmid et al [29] showed that, during L-T 4 replacement, IGF-I and acid-labile subunit secretion increased in the patients with both primary and central hypothyroidism, while IGFBP-3 - only in those with primary hypothyroidism. In 2008, Akin et al [30] reported that GH-IGF axis was affected in the patients with subclinical hypothyroidism and that L-T 4 replacement therapy could prevent abnormalities related to GH-IGF axis in them.…”
Section: Discussionmentioning
confidence: 99%